2016
DOI: 10.1177/0885066616631325
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity Diagnosis With Organ Dysfunction, Mortality, and Resource Use Among Children Hospitalized With Infection in the United States

Abstract: While there was no difference in in-hospital mortality by obesity diagnosis, variation in organ dysfunction, hospital stay, and hospital charges according to obesity status was mediated by illness severity. Findings from this study have significant implications for targeted approaches to mitigate the burden of obesity on infection and sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Several studies have also demonstrated an increased risk of developing infection and sepsis with worse outcomes in infections compared to normal weight patients [11]. Surprisingly, in sepsis, obesity has been revealed in several studies to have better mortality outcomes compared to leaner patients.…”
Section: Table 1: the World Health Organization Body Mass Indices Clamentioning
confidence: 99%
“…Several studies have also demonstrated an increased risk of developing infection and sepsis with worse outcomes in infections compared to normal weight patients [11]. Surprisingly, in sepsis, obesity has been revealed in several studies to have better mortality outcomes compared to leaner patients.…”
Section: Table 1: the World Health Organization Body Mass Indices Clamentioning
confidence: 99%
“…For instance, hospitalized obese children under 20 years of age with sepsis had higher occurrence of organ dysfunction and longer hospitalization compared to normal weight patients, with no difference in in-hospital mortality. 17 Other pediatric studies have similarly not identified differences in mortality rate by obesity status, 17 19 although there have been reported differences in resource use and morbidity, including longer hospital stay for obese children with status asthmaticus 20 and higher rates of hospital-acquired infections in obese children undergoing mechanical ventilation. 18…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have shown an association between obesity and poor outcomes in infectious diseases and sepsis 13‐16 . Another study evaluating the influence of obesity on sepsis reported no difference in mortality among patients with and without obesity 17 . Finally, some studies have also demonstrated a protective effect with improved outcomes, an entity often referred to as the ‘obesity survival paradox’ 7,13,18‐20 …”
Section: Introductionmentioning
confidence: 99%